Exchange and experimentation: community seed banks strengthen farmers' seed systems in Northern Malawi. Issue 7 (15th December 2022) - Vansant, Emilie C.; Bezner Kerr, Rachel; Sørensen, Helle; Phiri, Isaiah; Westengen, Ola T.
ABSTRACT: In Sub-Saharan Africa, the cultivation of local crop varieties persists despite a political environment that favours commercial seed system development to address seed and food insecurity. Community seed banks (CSBs) are emergent alternative/complementary development initiatives, yet there remains limited empirical research on their role in farmers' seed systems. In Malawi, where maize is a sociopolitical currency, we use maize seeds as a means to examine how CSBs may support farmers' seed systems. Through 60 semi-structured interviews with both CSB members and non-members, we collected quantitative and qualitative data on maize seed access opportunities, farmer preferences, and patterns of seed adoption/discontinuation. Interviews show that while CSBs play a negligible role in farmers' maize seed supply, they can strengthen seed sharing networks through auxiliary social and economic services. CSB members report higher levels of satisfaction with local maize over commercial maize, suggesting CSBs can expand farmers' frame of reference through events that encourage exchange and experimentation. Local power dynamics can affect CSB accessibility; initiatives to expand CSB operations must therefore address the inherent exclusivity of CSBs as membership-based institutions. These findings invite future research on CSB viability and the potential of decentralized development interventions to improve farmers' seed security in Sub-Saharan Africa.